TOR EGIL FØRLAND, Values, Objectivity, and Explanation in Historiography, New York – London 2017, Routledge, 194 pp., ISBN 978-1-138-20373-0 - Zeleňák, Eugen (Dějiny – teorie – kritika, 2018)
Book review